A Freshwater Fish-Based Diet Alleviates Liver Steatosis by Modulating Gut Microbiota and Metabolites: A Clinical Randomized Controlled Trial in Chinese Participants With Nonalcoholic Fatty Liver Disease. (17th October 2022) - He, Kaiyin; Guo, Li-Liangzi; Tang, Huijun; Peng, Xiaojuan; Li, Juan; Feng, Shufen; Bie, Caiqun; Chen, Weiwei; Li, Yuting; Wang, Min; Tang, Shaohui
Abstract : INTRODUCTION: We aimed to assess the effects of 2 isoenergetic intervention diets (a freshwater fish-based diet [F group] or freshwater fish-based and red meat-based diets alternately [F/M group]) on liver steatosis and their relationship with intestinal flora in patients with nonalcoholic fatty liver disease (NAFLD). METHODS: In this open-label, 84-day randomized controlled trial, 34 NAFLD patients with hepatic steatosis ≥10% were randomly assigned to the F group or F/M group in a 1:1 ratio using a computer-generated random number allocation by a researcher not involved in the study. Liver fat content and gut microbiota and its metabolites were measured. RESULTS: At the end of intervention, the absolute reduction of hepatic steatosis was significantly greater in the F group than in the F/M group (−4.89% vs −1.83%, P = 0.032). Of the 16 secondary clinical outcomes, the improvement in 7 in the F group was greater compared with the F/M group, including alanine aminotransferase and gamma-glutamyl transferase. Furthermore, dietary freshwater fish and red meat consumption alternately did not exacerbate NAFLD. Moreover, changes in the enrichment of Faecalibacterium, short-chain fatty acids, and unconjugated bile acids and the depletion of Prevotella 9 and conjugated bile acids in the F group were significantly greater compared with the F/M group. DISCUSSION: Higher intake of freshwater fish may be beneficial to NAFLD by regulating gut microbiota and its metabolites, whereas intake of a similar total of animal protein and fat from the alternating freshwater fish and red meat may not be harmful for NAFLD in the dietary management of patients with NAFLD. Abstract :